THE CONCEPT OF THE LEADER WOMAN’S IMAGE AND THE PSYCHOLOGICAL CHARACTERISTICS OF ITS FORMATION (Scientific journal of the Fergana State University, 2024)
The article examines the specific psychological characteristics of the behavior and activities of women leaders. The definition of modern leadership abilities, as well as the characteristics and qualities of their manifestation in women, is considered. The article also reveals the socio-methodological foundations and essence of expanding the ranks of women leaders in New Uzbekistan.